The politics of piracy: political ideology and the usage of pirated online media - Graf-Vlachy, Lorenz; Goyal, Tarun; Ouardi, Yannick; Koenig, Andreas (Information Technology & Management, 2021)
There is a lack of clarity in information systems research on which factors lead people to use or not use technologies of varying degrees of perceived legality. To address this gap, we use arguments from the information systems and political ideology literatures to theorize on the influence of individuals’ political ideologies on online media piracy. Specifically, we hypothesize that individuals with a more conservative ideology, and thus lower openness to experience and higher conscientiousness, generally engage in less online media piracy. We further hypothesize that this effect is stronger for online piracy technology that is legally ambiguous. Using clickstream data from 3873 individuals in the U.S., we find that this effect in fact exists only for online media piracy technologies that are perceived as legally ambiguous. Specifically, more conservative individuals, who typically have lower ambiguity intolerance, use (legal but ambiguously perceived) pirated streaming websites less, while there is no difference for the (clearly illegal) use of pirated file sharing websites.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Ambiguity intolerance; File sharing; Legal issues; Online streaming; Piracy; Political ideology